Drop dynamics in the inkjet printing process. (July 2018) - Wijshoff, Herman
Abstract: The inkjet printing process involves a chain of processes in many physical domains at different length and time scales. The final goal is the deposition of droplets of all kinds of fluids with any desired volume and velocity. To comply with the increasing and diverging requirements for today's inkjet technology, a fundamental understanding of the underlying processes is very important. By combining state of the art experimental and numerical techniques, the physics behind the chain of processes are being explored. The fundamental knowledge gained is crucial for the further development of the inkjet printing technology which became mature in graphical printing applications and plays a key role in many emerging new industrial and medical applications. Graphical abstract: Image 1 Highlights: very sharp optical recordings of fast moving micrometer sized droplets with iLIF acoustic detection of very small disturbances of the drop formation process the physics of an impacting, spreading, evaporation and absorbing droplet numerical simulations of the drying process of multi-component liquid drops multiscale simulations of contact line dynamics and particle depositions